Life safety culture: the concept and the problem of its formation in educational organizations - E. A. Panina (Вестник Майкопского государственного технологического университета)
Life safety culture is considered to be one of the most important components of basic general education in modern conditions. Its main vector is focused on adequately solving the priority tasks of ensuring personal and national security. In this regard, the scientific problem considered in this article seems to be relevant and in demand in modern educational practice, because the effectiveness of ensuring the safety of the entire world community depends on the level of development of the life safety culture of each person.   The problem of the research is to identify the content of the category “life safety culture” and the theoretical basis for justifying the process of its formation among students in educational institutions.   The purpose of the research is to reveal the category “life safety culture” in various fields of knowledge and to substantiate the main theoretical determinants of its formation in educational institutions.   The following methods were used in the study: analysis and synthesis of scientific and methodological literature, methods of visual presentation of information. The results of the research contribute to the study of scientific and theoretical aspects of organizing the pedagogical process of forming a life safety culture in educational institutions, as well as scientific and theoretical approaches to substantiate the definition of «life safety culture».   Key conclusions. Three approaches to the content of the category “life safety culture” have been identified - social-philosophical, psychological and pedagogical ones; the prerequisites for constructing pedagogical influences on the formation of a culture of life safety in educational institutions have been indicated: principles (general and specific), and the directions ofthis activity have also been detected.